Legal Aspects of Hybrid Threats and Warfare - Zombory, Katarzyna (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
The chapter addresses the selected legal aspects of hybrid threats and warfare connected to certain branches of the international public and European Union (EU) law. The overarching objective of the chapter is to present a legal assessment of hybrid threats and delineate the scope of lawful countermeasures to respond to them, which is a prerequisite for swifter decision-making and enhancing the defensive capability of the EU. The author outlines the conceptual framework of hybrid warfare and hybrid threats, exemplified by the hybrid tactics used in the 2014 Russian invasion against Ukraine. The legal analysis of hybrid threats and warfare is carried out under rules governing the lawfulness of the resort to force (jus ad bellum), international law of armed conflicts (jus in bello, international humanitarian law), and human rights law. This analysis demonstrates that it is difficult to conclude whether the use of hybrid threats and warfare amounts to the use of force, and whether it triggers legal consequences attached to the existence of armed conflict, in terms of the right to self-defence and application of international humanitarian law, especially if a hybrid campaign does not involve the use of kinetic force. While balancing between war and peace, hybrid threats and warfare highlight how the traditional dichotomy underlying the law on the use of force works in favour of hybrid aggressors. Compared to the international legal framework, the EU’s framework “theoretically” offers wider possibilities for a collective response to hybrid threats and campaigns compared with the North Atlantic Treaty Organization (NATO). This is because the EU framework enables invocation of the mutual solidarity clause (Article 222 Treaty on the Functioning of the EU) in situations that otherwise would not trigger a collective defence mechanism under Article 5 NATO Treaty. Keywords: hybrid threats, hybrid warfare, information warfare, lawfare, collective defence